Antioxidant properties of Fragrea Acuminatissima Merr. using selected alcoholic solvents extraction - Kirubahshini Krshunan (2016)
Most indigenous plants in Malaysia are still underutilized and Fragrea Acuminatissima Merr.is one of the examples. This particular plant have been claimed to possess health benefits such as relieve muscle pain by the indigenous people at Gua Musang, Kelantan. This study is carried out to determine the antioxidant activity in stems of Fragrea Acuminatissima Merr.using different alcoholic solvent of different concentration (100% methanol, 80% methanol, 100% ethanol and 80% ethanol) and to evaluate the TPC and TFC of different solvents extraction of ragrea Acuminatissima Merr. The antioxidants activities of these plant extract were determined by using three different assays, DPPH radical scavenging activity, Ferric Reducing Antioxidant Power (FRAP) and ABTS assay. 100% methanol extract produced from the stems exhibit higher antioxidant content with high phenolic contents (908.17 µg GAE/mg) and total flavonoid contents (1571.003 µg QE/mg). Meanwhile, 100% ethanol stem extracts showed higher DPPH scavenging activity (IC50) value of 50 µg/ml) with no significant different with 100% methanolic extract and higher FRAP value of 126.13 µg TE/mg. The present findings showed total phenolic content (TPC) and total flavonoid content (TFC) moderately correlated with DPPH radical scavenging activity with TPC (r=0.543) and TFC (r=0.550) and ABTS TPC (0.488) and TFC (0.497). Whereas TPC and TFC are weakly correlated with FRAP with TPC (r=0.371) and TFC (r=0.307). Overall, the best extracting solvent for this plant can be concluded as 100% methanol.